Isolation and characterization of a molybdenum-reducing and SDSdegrading Klebsiella oxytoca strain Aft-7 and its bioremediation application in the environment - NORAZLINA MASDOR; MOHD SHUKRI ABD SHUKOR; AFTAB KHAN; MOHD IZUAN EFFENDI BINMOHD HALMI; SITI ROZAIMAH SHEIKH ABDULLAH; NOR ARIPIN SHAMAAN; MOHD YUNUS SHUKOR (Society for Indonesian Biodiversity, 2015)
Masdor N, Shukor MSA, Khan A, Halmi MIE, Abdullah SRS, Shamaan NA, Shukor MY. 2015. Taxonomy and distribution of species of the genus Acanthus (Acanthaceae) in mangroves of the Andaman and Nicobar Islands, India. Biodiversitas 16: 238-246.Pollution as a result of anthropogenic activities is a severe global issue. These activities including inappropriate disposal, industrialand prospecting activities and unnecessary use of agricultural chemicals have triggered international initiatives to eliminate thesecontaminants. In this work we screen the ability of a molybdenum-reducing bacterium isolated from contaminated soil to grow andreduce molybdenum on various detergents. The bacterium was able to grow on SDS as a carbon source although the compound did notsupport molybdenum reduction. The bacterium reduces molybdate to Mo-blue optimally between pH 5.8 and 6.3 and between 25 and34oC. Glucose was the best electron donor for supporting molybdate reduction followed by sucrose, D-mannitol, D-sorbitol, lactose,salicin, trehalose, maltose and myo-Inositol in descending order. Other requirements include a phosphate concentration between 5.0 and7.5 mM and a molybdate concentration between 5 and 20 mM. The absorption spectrum of the Mo-blue produced was similar toprevious Mo-reducing bacterium, and closely resembles a reduced phosphomolybdate. Molybdenum reduction was inhibited by mercury(ii), silver (i) and copper (ii) at 2 ppm by 62.1, 33.9 and 33.6%, respectively. Biochemical analysis resulted in a tentative identificationof the bacterium as Klebsiella oxytoca strain Aft-7. The ability of this bacterium to detoxify molybdenum and degrade detergent makesthis bacterium an important tool for bioremediation.